Identification of Inhaler Technique Errors Among Asthmatic Patients - Brwa Omer Sharif; Bnar Saleh Ismael; Naza Shakir Shareef Shekhany (Zanco Journal of Pure and Applied Sciences, 2023)
Proper inhaler technique is a fundamental problem that directly relates to asthma control. Adequate inhaler administration is influenced by a variety of factors, including patient- and device-related factors. Of these factors, device-related errors are more prevalent, and their resolution helps to control illness. A cross sectional, study has been done by using a structured questionnaire form hospital outpatient setting, 70 patients participated using pressurized metered dose inhaler and dry powder inhalers their technique was evaluated face to face, the most common steps of error are detected, and the data analyzed using the SPSS program.  Patients who used the proper inhaler technique (7.1% controlled) were in a better control state than those who used the erroneous inhaler technique (28.6% controlled and 62.9% uncontrolled), (p-value 0.011). Overall, the most frequent mistakes were failing to softly exhale before using an inhaler (50%), failing to hold one's breath for five seconds (50%), failing to breathe inappropriately (52.9%), and failing to clean the mouthpiece (65.7%). Specific errors varied across inhaler types, with the most errors observed for pMDI inhalers. In short, using an inhaler correctly is essential for managing and monitoring asthma control. Most people use their inhalers incorrectly, which results in uncontrolled disease.